Relationship between Endogenous, Transgene FVIII Expression and Bleeding Events Following Valoctocogene Roxaparvovec Gene Transfer for Severe Hemophilia A: A Post-Hoc Analysis of the GENEr8-1 Phase 3 Trial - Pipe, Steven W; Ozelo, Margareth C; Kenet, Gili; Reding, Mark T; Mason, Jane; Leavitt, Andrew D; Madan, Bella; Laffan, Michael; Quon, Doris V.; von Drygalski, Annette; Chou, Sheng-Chieh; Shapiro, Susan; et al. (Blood, 2021)
▪ Introduction. Valoctocogene roxaparvovec (AAV5-hFVIII-SQ) is an adeno-associated virus gene therapy that transfers a B-domain deleted factor VIII (FVIII) cDNA to hepatocytes. The open-label, single-arm, multicenter phase 3 GENEr8-1 trial (NCT03370913) evaluated valoctocogene roxaparvovec in 134 men with severe hemophilia A (HA) and demonstrated an 83.8% reduction in annualized treated bleeding rate (ABR) and superiority to FVIII prophylaxis (P <0.001). The relationship between baseline FVIII activity and ABR was estimated in congenital HA (den Uijl, et al. Haemophilia 2011;17[1]:41-4); it is unknown if a similar relationship exists after gene transfer. We present here post-hoc analyses of transgene-derived FVIII activity and bleeds in GENEr8-1. Methods. Men ≥18 years of age with severe HA previously on FVIII prophylaxis who were negative for FVIII inhibitors and anti-AAV5 antibodies received one 6x10 13 vg/kg infusion of valoctocogene roxaparvovec. FVIII activity was measured by chromogenic substrate (CSA; lower limit of quantitation [LLOQ], 3.0 IU/dL) and one stage assays (OSA; LLOQ, 1.0 IU/dL); median FVIII activity in every 4- or 6-week window was assessed. Self-reported treated bleeds were counted after week 4, when routine prophylaxis was scheduled to end. The relationship between number of treated joint bleeds and matched median FVIII activity levels in each 4- or 6-week window was modeled using negative binomial regression. Results. As of the data cut date, mean follow-up was 71.6 weeks; 1 participant was lost to follow-up at week 66. At weeks 49-52 (latest time with data for all participants; intent-to-treat population), 9% (12/134) had CSA FVIII activity <3 IU/dL, 3% (4/134) had median FVIII activity ≥3-<5 IU/dL, 17% (23/134) had median FVIII activity ≥5-<15 IU/dL, and 71% (95/134) had median FVIII activity ≥15 IU/dL. While on FVIII prophylaxis prior to gene transfer, 32% of participants (43/134) had an ABR of 0. Following gene transfer, 75% of participants (101/134) were bleed-free through their last follow-up prior to the data cut. The remaining 33 participants reported 149 treated bleeds total, 62% (93/149) as traumatic and 38% (56/149) as spontaneous. By location, 53% (79/149) occurred in joints, 19% (28/149) in muscle, 14% (21/149) in soft tissue, and 14% (21/149) in other or unspecified locations. Relative to FVIII level, 54% of treated bleeds (80/149) occurred when CSA FVIII was <3 IU/dL (LLOQ), 12% (18/149) when FVIII was ≥3-<5 IU/dL, 23% (35/149) when FVIII was ≥5-<15 IU/dL, and 11% (16/149) when FVIII was ≥15 IU/dL. Of 16 treated bleeds that occurred when FVIII was ≥15 IU/dL, 13 were traumatic. Treated joint bleeds followed a similar pattern: 51% (40/79) occurred when FVIII was <3 IU/dL, 15% (12/79) when FVIII was ≥3-<5 IU/dL, 27% (21/79) when FVIII was ≥5-<15 IU/dL, and 8% (6/79) when FVIII was ≥15 IU/dL. A negative binomial regression model based on these data and matched FVIII activity levels predicts <1 treated joint bleed in 2 years for individuals treated with valoctocogene roxaparvovec with FVIII activity ≥15 IU/dL (CSA; Figure). Clinical value of the CSA at low FVIII levels is limited by its LLOQ of 3 IU/dL. Of 12 participants with median FVIII levels below the CSA LLOQ at weeks 49-52, 9 had improved or the same ABR post-gene therapy relative to prophylaxis. The OSA, with its LLOQ of 1 IU/dL, provided important information here. By OSA, 1 had FVIII <1 IU/dL, 5 had FVIII ≥1-<5 IU/dL, and 3 had FVIII ≥5 IU/dL. The remaining 3 participants who had increased ABR after gene transfer had FVIII levels by OSA of 0, 2.1, and 4.8 IU/dL. For participants with OS FVIII <5 IU/dL at week 52 (n = 11), median (IQR) ABR was 1.2 (0-7.9), similar to the median (IQR) ABR of 1.6 (0.6-3.5) reported for people with moderate HA (Abdi, et al. J Throm Haemost 2020;18[12]:3203-10). Conclusions. Gene transfer with valoctocogene roxaparvovec led to sustained endogenous FVIII production and reduced ABR in this phase 3 trial. After gene transfer, the majority of bleeds were traumatic. When FVIII was ≥15 IU/dL, reports of treated bleeds, including joint bleeds, were rare. CSA FVIII activity was predictive of bleeding risk post-gene transfer, as for epidemiologic congenital HA results. At FVIII levels below the CSA LLOQ, the OSA provided clinically relevant information; bleeding with OSA FVIII <5 IU/dL was similar to observations in people with moderate HA, though further exploration with more data is needed. [Display omitted] Pipe: Biomarin: Consultancy, Other: Clinical trial investigator; Regeneron/ Intellia: Consultancy; uniQure: Consultancy, Other; Spark Therapeutics: Consultancy; Takeda: Consultancy; Sanofi: Consultancy, Other; Sangamo Therapeutics: Consultancy; Roche/Genentech: Consultancy, Other; Pfizer: Consultancy; Novo Nordisk: Consultancy; Freeline: Consultancy, Other: Clinical trial investigator; HEMA Biologics: Consultancy; CSL Behring: Consultancy; Catalyst Biosciences: Consultancy; Genventiv: Consultancy; Grifols: Consultancy; Bayer: Consultancy; ASC Therapeutics: Consultancy; Apcintex: Consultancy; Octapharma: Consultancy; Shire: Consultancy. Ozelo: BioMarin Pharmaceutical Inc.: Consultancy, Other: Clinical trial investigator, Speakers Bureau; Bayer: Consultancy, Speakers Bureau; Novo Nordisk: Consultancy, Other: Clinical trial investigator, Travel support, Speakers Bureau; Pfizer: Consultancy, Other: Clinical trial investigator, Research Funding; Roche: Consultancy, Other: Clinical trial investigator, Travel support, Research Funding, Speakers Bureau; Sanofi: Consultancy, Other: Clinical trial investigator; Takeda: Consultancy, Other: Clinical trial investigator, Travel support, Research Funding, Speakers Bureau; Grifols: Other: Grants review. Kenet: Takeda: Consultancy; Roche: Consultancy; Novo Nordisk: Consultancy; Shire: Research Funding; Pfizer: Consultancy, Research Funding; Opko Biologics: Research Funding; Bayer: Consultancy, Research Funding; Alnylam: Consultancy, Research Funding. Reding: Bayer, CSL Behring, Sanofi Genzyme, Takeda: Speakers Bureau; Bayer, Biomarin (institutional research funding): Research Funding; Bayer, CSL Behring, NovoNordisk, Sanofi Genzyme, Takeda: Honoraria; Bayer, CSL Behring, NovoNordisk, Sanofi Genzyme, Takeda (advisory committees): Membership on an entity's Board of Directors or advisory committees. Mason: BioMarin Pharmaceutical Inc.: Other: Participation as a clinical trial investigator; Roche: Other: Participation as a clinical trial investigator, Travel support, Speakers Bureau. Leavitt: Syntimmune: Research Funding; Sangamo Therapeutics: Research Funding; Pfizer: Research Funding; Merck: Consultancy; CSL DOVA: Consultancy; Catalys: Consultancy; BioMarin: Consultancy, Research Funding; BPL: Consultancy; Behring: Consultancy; HEMA Biologics: Consultancy; Rigel: Consultancy. Laffan: Shire: Membership on an entity's Board of Directors or advisory committees; Leo-Pharma: Speakers Bureau; Alexion: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Roche: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Takeda: Speakers Bureau; AstraZeneca: Consultancy; Sobi: Membership on an entity's Board of Directors or advisory committees, Other: Travel support; Bayer: Other: Travel support, Speakers Bureau; Pfizer: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; BioMarin Pharmaceutical Inc.: Research Funding. Quon: Orthopaedic Institute for Children: Current Employment. von Drygalski: Takeda: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Hematherix, Inc: Membership on an entity's Board of Directors or advisory committees, Patents & Royalties: Super FVa; Novo Nordisk: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Pfizer: Research Funding; CSL Behring: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Biomarin: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Sanofi: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; uniQure: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Genentech: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau. Chou: Bayer: Other: Clinical trial investigator, Speakers Bureau; Novo Nordisk: Consultancy, Other: Clinical trial investigator, Speakers Bureau; BioMarin: Other: Clinical trial investigator; Sanofi: Consultancy, Other: Clinical trial investigator, Speakers Bureau; Chugai: Consultancy, Other: Clinical trial investigator, Speakers Bureau; Pfizer: Other: Clinical trial investigator, Speakers Bureau; CSL: Consultancy, Other: Clinical trial investigator, Speakers Bureau. Shapiro: Sobi: Consultancy; Shire: Consultancy; Pfizer: Consultancy, Speakers Bureau; Bayer: Other: Travel support, Speakers Bureau; Takeda: Speakers Bureau; Roche: Speakers Bureau; CSL Behring: Other: travel support. Dunn: Genentech/Roche: Consultancy, Speakers Bureau; ATHN: Research Funding; Biomarin: Consultancy, Research Funding; Freeline: Research Funding; Takeda: Research Funding; World Federation of Hemophilia USA: Membership on an entity's Board of Directors or advisory committees; CSL Behring: Consultancy; Uniqure: Consultancy; Sanofi: Research Funding; Kedrion: Consultancy. Wang: Bioverativ: Consultancy, Other: Clinical trial investigator; CSL Behring: Consultancy, Other: Clinical trial investigator; Novo Nordisk: Consultancy, Other: Clinical trial investigator; Genentech: Consultancy, Other: Clinical trial investigator; Takeda: Consultancy, Other: Clinical trial investigator; Hema Biologics: Consultancy, Other: Clinical trial